Efectos de la aplicación del fertilizante Microessentials sobre el comportamiento agronómico del pasto humidicola (Brachiaria humidicola) en la zona de Babahoyo - Mejía Martínez, Carlos Manuel (2015)
The grass humidicola (Brachiaria humidicola) it is a perennial gramineous grass with growth estolonifer, it grows in places of height from 0 to 1800 m and precipitations 600 mm from now on, it possesses a wide range of adaptation, bigger quantity of forage and superior nutritional quality. In Ecuador the III National Agricultural Census registers that 41% of agricultural use is dedicated to grass at the 2000 you crop 5´087.132,00 hectares per year with an average 100 tons for hectárea/año. The objective of this investigation was to measure the effects of the application of the fertilizer microessentials on the agronomic behavior of the grass Brachiaria humidicola, additionally he/she was carried out an economic analysis. The work was carried out in the lands of the Ability of Agricultural Sciences, located in the Kilometer 7,5 of the road Babahoyo-Montalvo. Ten treatments were investigated, with 4 repetitions........